Direct Electrochemistry of Bilirubin Oxidase from Magnaporthe orizae on Covalently‐Functionalized MWCNT for the Design of High‐Performance Oxygen‐Reducing Biocathodes. Issue 33 (15th May 2018) - Gentil, Solène; Carrière, Marie; Cosnier, Serge; Gounel, Sébastien; Mano, Nicolas; Le Goff, Alan
Abstract: Herein, the direct electrochemistry of bilirubin oxidase from Magnaporthe orizae ( Mo BOD) was studied on CNTs functionalized by electrografting several types of diazonium salts. The functionalization induces favorable or unfavorable orientation of Mo BOD, the latter being compared to the well‐known BOD from Myrothecium verrucaria ( Mv BOD). On the same nanostructured electrodes, Mo BOD can surpass Mv BOD in terms of both current densities and minimal overpotentials. Added to the fact that Mo BOD is also highly active at the gas‐diffusion electrode (GDE), these findings make Mo BOD one of the MCOs with the highest catalytic activity towards the oxygen reduction reaction (ORR). Abstract : Go electro ! The direct electrochemistry of bilirubin oxidase from Magnaporthe orizae ( Mo BOD) was studied on carbon nanotubes (CNTs) functionalized by electrografting several types of diazonium salts (see figure). On the same nanostructured electrodes, Mo BOD can surpass Mv BOD in terms of both current densities and minimal overpotentials. These findings make Mo BOD, one of the MCOs with the highest catalytic activity towards the oxygen reduction reaction (ORR).